Ecotoxicological effects of microplastics and adsorbed contaminants on aquatic organisms - Dioses-Salinas, Diana; Universidad San Ignacio de Loyola, Lima. (2019)
Microplastic (< 5 mm) pollution have raised concern on behalf of the scientific community and the general public. Microplastic occurrence in aquatic environments and organisms have been well documented. However, it is in recent years that the ecotoxicological effects of microplastics have begun to be studied. The aim of the present study was to review, evaluate and discuss the current state of art regarding microplastic and related contaminants ecotoxicological effects in microalgae, crustaceans, molluscs and fish. The results of previous studies have proven growth inhibition and chlorophyll-a decrease in microalgae. Ingestion by small crustaceans and population reduction have been evidenced. Biomarkers in bivalves and fish have shown neurotoxic effects and oxidative stress, along with abnormal behavior. The current state of art lacks realistic parameters and microplastic concentrations to assess environmental pollution. The need for further research was discussed.